Hybrid Composite of Inorganic Oxide (TiO2:WO3) for Remove Methyl Blue and Methyl Orange by Adsorption/Photo degradation Reaction - Baraa Kasim Mohammed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Semiconductor inorganic oxides such as titanium dioxide and tungsten trioxide are widely used in environmental remediation due to their stability and photocatalytic properties for pollutant removal. Specific Background: Binary TiO₂:WO₃ composites provide synergistic semiconductor behavior supporting adsorption and ultraviolet-assisted photodegradation of dye pollutants in aqueous media. Knowledge Gap: However, comparative removal performance toward methyl orange and methylene blue using combined adsorption and photocatalytic processes remains insufficiently clarified. Aims: This study prepared a TiO₂:WO₃ composite using TiOSO₄ precipitation with hydrogen peroxide and evaluated its activity toward removal of methyl orange and methylene blue. Results: X-ray diffraction and Raman spectroscopy confirmed anatase, rutile, and WO₃ phases, while removal performance exceeded 80 percent for methyl orange and showed lower activity for methylene blue under combined processes. Novelty: The study demonstrates synergistic binary oxide activity supported by structural characterization and comparative dye removal behavior. Implications: The results support TiO₂:WO₃ composites as suitable materials for adsorption and photocatalytic dye removal applications in aqueous treatment systems. Highlights: • TiO₂ WO₃ Hybrid Structure Confirmed by XRD and Raman Characterization• Binary Oxide System Shows Higher Removal Performance for Methyl Orange Than Methylene Blue• Combined Adsorption and Ultraviolet-Assisted Reaction Achieves Removal Above 80 Percent Keywords: Titanium Dioxide, Tungsten Trioxide, Binary Oxide Composite, Photodegradation, Dye Removal.